Rebellion on Hvar island (1510–1514). People’s revolt or Venetian manipulation? - Wróbel, Piotr (Balcanica Posnaniensia. Acta et studia, 2023)
In the extensive work of the Dubrovnik-born Benedictine Lodovico Tuberon de Crieva, „Commentaria de temporibus suis” describing the events in the Mediterranean in the years 1490–1522, there is a small passage about the events on the island of Hvar (ital. Lesina). The island was then, together with most of the Dalmatian coast, under the rule of the Venetian Republic. On Hvar in 1510, a popular uprising against the local nobles broke out, which lasted with varying intensity until 1514. The Venetian authorities then sent considerable armed forces, which, after defeating the rebels at sea and on land, suppressed the rebellion. It is surprising, however, that Tuberon suggests in the above-mentioned passage that the outbreak of the revolt could have been provoked by the Venetians themselves, who feared the nobility allegedly favoring the King of Hungary. He also mentions the leading role of a clergyman who was supposed to encourage the plebs to act and initiate a revolt. Taking the mentioned text of Tuberon as a starting point, the author analyzes the political and social situation on the island of Hvar as well as the background and course of the events in the years 1510–1514. The author's goal is to establish what the grounds for Tuberon's presumptions were and to what extent they are true.